2012
DOI: 10.1007/s11239-012-0759-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between B-group vitamins and venous thrombosis: systematic review and meta-analysis of epidemiological studies

Abstract: A homocysteine-independent role for B-group vitamins on venous thrombosis (VT) development has been reported. However, related research findings remain inconsistent. PUBMED, EMBASE, and COCHRANE databases were searched to collect information on all eligible studies to make a meta-analysis about the relationship between B-group vitamins and VT. Literature search results did not suggest a correlation between thiamin, pantothenic acid, niacin, or riboflavin with VT. Based on their correlations in the literature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…Rivaroxaban inhibits both free and clot-bound factor Xa, as well as prothrombinase activity. 45 High homocysteine and B vitamin deficiency in the presence of MTHFR C677T homozygosity or compound C677T-A1298C heterozygosity are prothrombotic, 46 and high homocysteine can be normalized by L-methylfolate-vitamin B6-vitamin B12 therapy with reduction of thrombotic potential. 47,48 The authors have studied 300 patients with idiopathic hip ON 9,49-52 but have en-countered only 15 with idiopathic ON limited solely to the knees, demonstrating its rarity, the need for investigation of its etiology, and the need for development of improved treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Rivaroxaban inhibits both free and clot-bound factor Xa, as well as prothrombinase activity. 45 High homocysteine and B vitamin deficiency in the presence of MTHFR C677T homozygosity or compound C677T-A1298C heterozygosity are prothrombotic, 46 and high homocysteine can be normalized by L-methylfolate-vitamin B6-vitamin B12 therapy with reduction of thrombotic potential. 47,48 The authors have studied 300 patients with idiopathic hip ON 9,49-52 but have en-countered only 15 with idiopathic ON limited solely to the knees, demonstrating its rarity, the need for investigation of its etiology, and the need for development of improved treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that low levels of pyridoxal-5-phosphat, the coenzyme form vitamin B 6 < 21, 7 nmol/L gave a twofold higher thrombotic risk [ 35 ]. In addition, Zhou et al [ 36 ] reported that there may be a homocysteine-independent role for B-group vitamins in venous thrombosis development. Our finding supports opinion that it may be possibly a homocysteine-independent relationship between low vitamin B 6 level and venous thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Hyperhomocysteinemia due to reduced B-group vitamins (folic acid, vitamin B12, and vitamin B6) levels is thought to be a part of the pathophysiologic link between B-group vitamins and venous thrombosis. 6 Besides, Methylenetetrahydrofolate reductase (MTHFR) gene mutations were supposed to increase the risk of DVT. Increased hyperhomocysteinemia (sometimes be related with MTHFR mutations) seems to be responsible for increased risk of thrombosis.…”
Section: Introductionmentioning
confidence: 99%